The Still Underestimated Problem of Fungal Diseases Worldwide - Almeida, Fausto; Rodrigues, Marcio L.; Coelho, Carolina (Frontiers in Microbiology, 2019)
In the past few years, fungal diseases caused estimated over 1.6 million deaths annually and over one billion people suffer from severe fungal diseases (Brown et al., 2012; Anonymous, 2017b). Public health surveillance of fungal diseases is generally not compulsory, suggesting that most estimates are conservative (Casadevall, 2017; Anonymous, 2017a). Fungal disease can also damage plants and crops, causing major losses in agricultural activities and food production (Savary et al., 2012). Animal pathogenic fungi are threatening bats, amphibians and reptiles with extinction (Casadevall, 2017). It is estimated that fungi are the highest threat for animal-host and plant-host species, representing the major cause (approximately 65%) of pathogen-driven host loss (Fisher et al., 2012). In this complex scenario, it is now clear that the global warming and accompanying climate changes have resulted in increased incidence of many fungal diseases (Garcia-Solache and Casadevall, 2010). On the basis of all these factors, concerns on the occurrence of a pandemic of fungal origin in a near future have been raised (Casadevall, 2017). In this context, to stop forgetting and underestimating fungal diseases is mandatory.